2012
DOI: 10.22358/jafs/66078/2012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of supplementing diets with <i>Atractylodes macrocephala</i> Koidz rhizomes on growth performance and immune function in piglets

Abstract: The rhizome of Atractylodes macrocephala Koidz (baizhu in Chinese, AMK) is a well-known traditional Chinese medicine that has long been used as a digestive and tonic. The experiment was conducted to investigate the effect of baizhu powder on the growth performance and immune function of piglets. Duroc × Landrace×Yorkshire piglets (n=72, half males and half females, 42 days of age, liveweight 14.82±0.17 kg) were randomly allocated to three treatments: control, control+AMK either ground (GMD=180 μm), or microniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…TCM formulations as dietary supplements have positive effects on the growth performance of piglets: previous reports have demonstrated that dietary supplementation with the TCM herbs can increase average daily feed intake and ADG, improve the gain/feed ratio, and reduce the incidence of diarrhea in weaned piglets (Chen et al, 2007;Lin et al, 2013;Xu et al, 2012;Zhao et al, 2015;Jian et al, 2007). Here, our results suggest that the LMT group manifested a significant increase in ADG, and the FCR tended to diminish in these piglets as compared to that in the LC group, in agreement with previous research (Lai et al, 2015;Gui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…TCM formulations as dietary supplements have positive effects on the growth performance of piglets: previous reports have demonstrated that dietary supplementation with the TCM herbs can increase average daily feed intake and ADG, improve the gain/feed ratio, and reduce the incidence of diarrhea in weaned piglets (Chen et al, 2007;Lin et al, 2013;Xu et al, 2012;Zhao et al, 2015;Jian et al, 2007). Here, our results suggest that the LMT group manifested a significant increase in ADG, and the FCR tended to diminish in these piglets as compared to that in the LC group, in agreement with previous research (Lai et al, 2015;Gui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, Baizhu is allowed to be developed and applied as a functional food by the National Health Commission, People's Republic of China ( 3 ). Scholarly research has shown that AM rhizome possesses a variety of biological activities, such as improving gastrointestinal ( 4 ), immunomodulatory ( 5 ), anti-Alzheimer's ( 6 ), anti-inflammatory ( 7 ), and anti-tumor activities ( 8 ). To date, about 230 members have been reported in AM rhizome, of which terpenoids and their glycosides are the main active ingredients ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are classified as complementary and alternative medicines and are regulated by the Therapeutic Goods Administration in Australia and the Dietary Health and Supplement Education Act under the Food and Drug Administration in the USA [ 11 , 12 , 13 , 14 , 15 ]. As feed additives, plant-derived medicines play an important role in promoting growth, anti-inflammatory, increasing immunity, and other functions [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%